DESCRIPTION OF THE LEVEL OF STRESS OF STUDENTS IN FACING THE THESIS AT ANESTHESIOLOGY NURSING STUDY PROGRAM APPLIED UNDERGRADUATE PROGRAM AT UNIVERSITY OF HOPE NATION PURWOKERTO - Ramadhan, Iqbal; Nova Handayani, Rahmaya; Burhan, Asmat; Anton Suhendro (Global Indonesia Health Care (GOICARE), 2024)
Background: Final year students often experience stress with final assignments, especially health students who are temporarily working on a thesis. Health students are also prone to experiencing stress when compiling a thesis and if not handled properly it will have an impact on the obstruction of thesis preparation, decreasing academic grades, and graduating not on time. Student stress can have a negative impact on academic grades, depression, and can even lead to dangerous actions such as suicide. Purpose: This study aims to determine the level of student stress in facing the thesis in the anesthesiology nursing study program of the applied undergraduate program at Harapan Bangsa University. Methods: This research includes descriptive quantitative research. This type of research is descriptive observational research with a cross sectional approach. Data analysis using Univariate analysis. The sampling technique in this study used convenience sampling. Result: Based on the results of this study, students who experienced a normal level of stress were 42 (42%) respondents, a description of the characteristics of respondents based on gender and age at the stress level of Applied Bachelor of Anesthesiology Nursing students at Harapan Bangsa University found that 24 (38.1%) female respondents experienced a normal level of stress and 40 (40.8%) respondents aged 22 years experienced a normal level of stress. Conclusion: The conclusion of this study is that students experience normal levels of stress.